Pressure dependence of micro‐Raman mass spectrometry for carbon isotopic composition of carbon dioxide fluid. (2nd March 2020) - Yokokura, Lena; Hagiwara, Yuuki; Yamamoto, Junji
Abstract: Micro‐Raman spectroscopy can find the carbon isotopic ratio of CO2 fluid from the ratio of intensity or area of a 13 CO2 peak to that of a 12 CO2 peak. We examined the precisions of carbon isotopic ratios (δ 13 C) of CO2 at constant room temperature and pressure of 10–150 MPa. Measurement of the intensity ratio has precision of 2.8–8.7‰, which is better than that of the area ratio of 4.5–14.7‰. We also investigated the pressure dependence of the Raman intensity ratios and area ratio by changing fluid pressure. When changing fluid pressure from 10 to 150 MPa, the ratios of intensity and area both show negative correlation with fluid pressure (CO2 density). Pressures of two types affect the Raman spectrum of CO2 peaks, affecting the peak position and peak shape. To evaluate effects on the peak position, we repeatedly measured the intensity ratio at constant CO2 pressure (10 MPa) with movement of the grating center position, which is defined as the center value of the analyzed wave number range. Although we moved the grating center position from 1, 248.5 to 1, 251.5 cm −1, no significant correlation was observed for either ratio of intensity or area. The pressure effect on the ratios can be corrected by ascertaining the CO2 pressure. Combination with the Raman spectroscopic barometry for CO2 enables analyses of δ 13 C of CO2 respectively using the intensity ratio and the area ratio of CO2 Raman peaks within 8.7 and 14.7‰. Abstract : Micro‐Raman spectroscopy can find the carbon isotopic ratio of CO2 fluid from the ratio of intensity or area of a 13 CO2 peak to that of a 12 CO2 peak. We investigated the pressure‐dependence of the Raman intensity ratios and area ratios by changing fluid pressure. When changing fluid pressure from 10 to 150 MPa, the ratios of intensity and area both show negative correlation with fluid pressure. The pressure effect on the ratios can be corrected by ascertaining the CO2 pressure.